The Importance of Literature in Modern Society - Mansurkhodjayeva Madina Toirjon qizi (Genius Journals, 2022)
The article deals with literature as an important science in linguistics. For the majority of people around the world, our first serious encounter with literature comes from school. Reading and writing has been drilled in all of us from an early age and this is set in motion with the start of examinations.
Keywords: Student’s perspective; ever-growing culture; better understanding of culture; complexity of human conflict